2016
DOI: 10.1016/j.ymgmr.2016.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Association of somatic burden of disease with age and neuropsychological measures in attenuated mucopolysaccharidosis types I, II and VI

Abstract: IntroductionThe mucopolysaccharidoses (MPSs) are a group of rare genetic lysosomal disorders with progressive multisystem involvement. An MPS-specific physical symptom scale was developed and introduced a Physical Symptom Score (PSS) to quantify the somatic disease burden across MPS I, II and VI.HypothesisSomatic burden of disease in patients with attenuated MPS I, II and VI as measured by the PSS will be positively associated with age and negatively associated with neuropsychological functions [i.e. full scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 16 publications
(21 reference statements)
0
8
0
3
Order By: Relevance
“…The extent of systemic disease burden may act as a predictor of cognitive performance in patients with attenuated MPS I. Recently, Ahmed et al [ 25 ] demonstrated that, in attenuated MPS I Hurler/Scheie (HS) and MPS IS, somatic disease burden measured by the Physical Symptom Score (PSS) was negatively associated with cognitive level (full-Scale IQ) ( p < 0.001), indicative that both measures reflect disease severity [ 25 ]. In addition, physical disease and sensorial defects cause functional impairment and reduce academic performances in attenuated MPS I individuals.…”
Section: Developmental and Behavioral Patterns Of Mpsmentioning
confidence: 99%
“…The extent of systemic disease burden may act as a predictor of cognitive performance in patients with attenuated MPS I. Recently, Ahmed et al [ 25 ] demonstrated that, in attenuated MPS I Hurler/Scheie (HS) and MPS IS, somatic disease burden measured by the Physical Symptom Score (PSS) was negatively associated with cognitive level (full-Scale IQ) ( p < 0.001), indicative that both measures reflect disease severity [ 25 ]. In addition, physical disease and sensorial defects cause functional impairment and reduce academic performances in attenuated MPS I individuals.…”
Section: Developmental and Behavioral Patterns Of Mpsmentioning
confidence: 99%
“…ERT has proven to be clinically effective in MPS patients, demonstrating an improvement in their range of motion, respiratory functions, cardiac functions, hearing, visual acuity, pain control and QoL [ [19] , [20] , [21] ]. Currently, elosulfase alfa and galsulfase are the only licensed ERT for patients with MPS-IVA and MPS-VI, respectively [ [22] , [23] , [24] , [25] , [26] ].…”
Section: Introductionmentioning
confidence: 99%
“…A Mucopolissacaridose VI (MPS VI), também conhecida como Síndrome de Maroteaux-Lamy, é uma doença rara, hereditária, autossômica recessiva, com mutação no gene ARSB, caracterizada pela deficiência na enzima lisossomal arisulfatase B, responsável pela degradação do dermatan sulfato, com isso progressivamente é acumulado o substrato intracelular, provocando as complicações multissistêmicas dos portadores [1][2][3][4][5][6][7][8][9].…”
Section: Introductionunclassified
“…Afeta ambos os sexos e a incidência mundial varia de 1: 230.000 a 1: 300.000 nascidos/vivos [6]. A MPS VI tem maiores registros no continente Europeu e América Latina, em particular em Portugal e no Brasil, sendo isto atribuído a distribuição migratória [8].…”
Section: Introductionunclassified
See 1 more Smart Citation